Kenya : Request for Stand-by Arrangement and an Arrangement Under the Standby Credit Facility. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2015)
Following the approval of a new constitution in 2010, the authorities have embarked on important reforms including fiscal devolution, VAT reform, and the overhaul of the expenditure management framework. Supported by a three-year ECF, which expired in December 2013 with all six reviews completed, Kenya has consolidated macroeconomic stability. Growth has been robust, inflation contained, debt remained sustainable and reserve buffers increased (Tables 1a and 1b and Figures 1 and 2). This progress in a market-friendly environment has continued to attract the interest of foreign investors. As a result, Kenya is recognized as a frontier market increasingly integrated in global financial markets. A Eurobond debut issue of USD 2 billion (the largest in SSA so far) took place successfully in June followed by a USD 750 million re-tap in December.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet